Policy Uncertainty, Trade, and Global Value Chains : Some Facts, Many Questions - Constantinescu, Cristina (World Bank, Washington, DC, 2019)
This paper attempts to quantify the impact of economic policy uncertainty on overall trade and trade linked to global value chains. Using new data on policy uncertainty for 18 countries and 24 years, it finds a statistically significant negative impact of policy uncertainty on overall trade growth. A 1 percent increase in uncertainty is associated with a 0.02 percentage point reduction in the growth of goods and services trade, implying that the increase in policy uncertainty since mid-2018 may have caused a 1 percentage point decline in world trade growth. The paper also finds that the impact of policy uncertainty on trade linked to global value chains is similar to overall trade. This is likely to be the result of two opposing forces: global value chains are more dependent on relation-specific investments that are sensitive to policy uncertainty, but these investments also make trade patterns sticky. More research and better data are needed to disentangle these different effects empirically.